Innovating digitally: The new texture of practices in Agriculture 4.0. Issue 2 (7th December 2021) - Lioutas, Evagelos D.; Charatsari, Chrysanthi
Abstract: This research aimed to identify the practices used by actors while innovating digitally in the field of agriculture. We also attempted to depict if and how they experience disruptions associated with the emergence of digital technologies. A qualitative research design permitted us to uncover that work‐ and system‐related disruptions follow the process of agricultural digitalisation. The study also indicated that innovating digitally is a collective process in which, however, some actors independently attempt to elevate their positions through weaving, that is, engaging in networking practices. On the other hand, despite their intense efforts to promote these technologies to farmers, innovation brokers, technology providers and researchers are not actively involved in the process of co‐creating value for and with farmers. We conclude by arguing that digital technologies are not scope‐neutral devices and by pointing out the need for redefining what responsibility means, what agricultural digitalisation research should stand upon and what it should stand for.